Broadband Channel Based on Polar Codes At 2.3 GHz Frequency for 5G Networks in Digitalization Era - Khoirun Ni'amah; Reni Dyah Wahyuningrum; Solichah Larasati (Universitas Medan Area, 2022)
This research using a polar code and without polar codes -based broadband channel that is affected by human blockage using one of the 5G cellular network frequencies at 2.3 GHz, 99 MHz bandwidth, 128 blocks of Fast Fourier Transform (FFT) with Cyclic prefix-Orthogonal Frequency Division Multiplexing ( CP-OFDM) and Binary Shift Keying (BPSK) modulation. The use of high frequencies causes the technology to be sensitive to the surrounding environment and attenuation such as human blockage. The purpose of this research is to determine the performance results and analyze the BER parameters that use polar codes and without polar codes on 5G network broadband channels that are affected by human blockage. Broadband channel modeling on a 5G network is presented in a representative Power Delay Profile (PDP) with the influence of human blockage, which is obtained as many as 41 paths which have multiple delays of 10 ns on each path. This research also uses the scaling method on representative PDP because the use of FFT will produce 128 blocks, and the results of this scaling show that there are 9 lanes with multiple delays of 50 ns. The results of this study are close to the average Bit Error Rate (BER) of 10-4. BER performance without polar code is affected by human blockage requires Signal to Noise (SNR) of 30 dB, for theory BER on BPSK modulation requires SNR of 34.5 dB and BER performance using polar code only requires SNR of 23 dB. These results indicate that using a polar code can reduce or save power usage by 7 dB without a polar codes. Polar codes can minimize errors in the 5G network system, because polar codes are one of the strong codes and are one of the channel coding recommended by ITU to be applied to 5G network systems